The clinical case for proton beam therapy - Foote, Robert L (BioMed Central, 2012)
ABSTRACT: Over the past 20 years, several proton beam treatment programs have been implemented throughout the United States. Increasingly, the number of new programs under development is growing. Proton beam therapy has the potential for improving tumor control and survival through dose escalation. It also has potential for reducing harm to normal organs through dose reduction. However, proton beam therapy is more costly than conventional x-ray therapy. This increased cost may be offset by improved function, improved quality of life, and reduced costs related to treating the late effects of therapy. Clinical research opportunities are abundant to determine which patients will gain the most benefit from proton beam therapy. We review the clinical case for proton beam therapy. SUMMARY SENTENCE: Proton beam therapy is a technically advanced and promising form of radiation therapy.